Analisis Pengaruh Konten Youtube terhadap Perkembangan Kemampuan Berbicara Anak - Hermawan, Dimas (ISOLEK: Jurnal Pendidikan, Pengajaran, Bahasa, dan Sastra, 2025)
Speaking ability is one of the language competencies that need to be developed from an early age. In the digital era, technology has become an inseparable part of children's lives. One of the widely used technology products is social media, such as YouTube. This study aims to analyze the influence of YouTube content on the development of children's speaking ability. The method used is qualitative with a phenomenological approach, interview techniques, and source triangulation as data analysis. The results of the study indicate that YouTube content has an effect on the development of children's speaking ability. Children who were previously quiet showed increased self-confidence and speaking skills after routinely watching the Queen Lala YouTube channel. However, the role of parents in supervising and limiting children's access to YouTube content is very important to maximize positive impacts and minimize negative impacts. This study is expected to provide insight to the public about the influence of YouTube content on children's speaking ability.